Inovações na atividade agrícola após a formação superior: um estudo em empreendimentos rurais do Município De São Martinho (RS) a partir de um enfoque neo-schumpeteriano - Amaral, Gilson Braz do (2017)
Innovations are produced through the conciliation of several factors and in several sectors, including agriculture, so that the accumulation of knowledge can potentiate its emergence. An understanding of innovations helps to understand economic and social development, even as a lot of studies have been produced with this focus. Among these, the work of the Neo-Schumpeterian authors has received significant attention, reinforcing in the economic analysis terms like complexity, limited rationality, technological progress, routines and knowledge, interpreting the articulation of these variables in the search of the economic actors to remain themselves in the market. This is the case of the present research, that, adding terms like innovation, agriculture and higher education, which seeks to apply the Neo-Schumpeterian approach in the identification of product and process innovations, produced by farmers living in the municipality of São Martinho (RS), who reached higher education, and also verified the results produced and the contribution of their higher education to the implementation of such innovations. The methodology used for the operationalization of the research consisted of an individual interview with rural producers, using a structured questionnaire to obtain data necessary to identify the innovations implemented, the contribution of higher education to the innovative process and the effects produced by the innovations. Thus, 113 innovations were identified, of which 15 product innovations were highlighted for the introduction of new cultivars, and 98 process innovations, mainly observed from changes in the management of the property. The effects produced by the innovations were classified in 16 groups, where it was observed that most of them promoted increase of the productive capacity. According to the interviews, it was observed that higher education had a significant contribution to the innovative process, both through general knowledge and specific training, as well as other sources of knowledge, in particular the experience of producers. With this, a relevant number of information about the innovations in the agricultural activity for the group studied was produced. The effects produced by the innovations were classified in 16 clusters, where it was observed that most of them promoted increase of the productive capacity. According to the interviews, it was observed that higher education had a significant contribution to the innovative process, both through general knowledge and specific training, as well as other sources of knowledge, in particular the experience of producers. With this, a relevant number of information about the innovations in the agricultural activity for the group studied was produced. Finally, it can be concluded that the neo-Schumpeterian approach reaches back on the observed reality and it was possible to visualize in the rural enterprises a significant variety of implemented innovations, both product and process. It was also possible to conclude that higher education, coupled with the practical experiences of rural producers, subsidized them to innovate.